Difference between revisions of "Chain Rule"

From Grad Wiki
Jump to navigation Jump to search
Line 4: Line 4:
 
But, what about more complicated functions?  
 
But, what about more complicated functions?  
  
For example, &nbsp;<math>f(x)=\sin(3x)</math>&nbsp; or &nbsp;<math>g(x)=(x+1)^8?</math>
+
For example, &nbsp;<math style="vertical-align: -5px">f(x)=\sin(3x)</math>&nbsp; or &nbsp;<math style="vertical-align: -5px">g(x)=(x+1)^8?</math>
  
 
Well, the key to calculating the derivatives of these functions is to recognize that these functions are compositions.  
 
Well, the key to calculating the derivatives of these functions is to recognize that these functions are compositions.  
  
For &nbsp;<math>f(x)=\sin(3x),</math>&nbsp; it is the composition of the function &nbsp;<math>y=3x</math>&nbsp; with &nbsp;<math>y=\sin(x).</math>
+
For &nbsp;<math style="vertical-align: -5px">f(x)=\sin(3x),</math>&nbsp; it is the composition of the function &nbsp;<math style="vertical-align: -4px">y=3x</math>&nbsp; with &nbsp;<math style="vertical-align: -5px">y=\sin(x).</math>
  
Similarly, for &nbsp;<math>g(x)=(x+1)^8,</math>&nbsp; it is the composition of &nbsp;<math>y=x+1</math>&nbsp; and &nbsp;<math>y=x^8.</math>
+
Similarly, for &nbsp;<math style="vertical-align: -5px">g(x)=(x+1)^8,</math>&nbsp; it is the composition of &nbsp;<math style="vertical-align: -5px">y=x+1</math>&nbsp; and &nbsp;<math style="vertical-align: -5px">y=x^8.</math>
  
 
So, how do we take the derivative of compositions?
 
So, how do we take the derivative of compositions?
Line 18: Line 18:
 
'''Chain Rule'''
 
'''Chain Rule'''
  
Let &nbsp;<math>y=f(u)</math>&nbsp; be a differentiable function of &nbsp;<math>u</math>&nbsp; and let &nbsp;<math>u=g(x)</math>&nbsp; be a differentiable function of &nbsp;<math>x.</math>&nbsp;  
+
Let &nbsp;<math style="vertical-align: -6px">y=f(u)</math>&nbsp; be a differentiable function of &nbsp;<math style="vertical-align: -1px">u</math>&nbsp; and let &nbsp;<math style="vertical-align: -6px">u=g(x)</math>&nbsp; be a differentiable function of &nbsp;<math style="vertical-align: -1px">x.</math>&nbsp;  
  
Then, &nbsp;<math>y=f(g(x))</math>&nbsp; is a differentiable function of &nbsp;<math>x</math>&nbsp; and  
+
Then, &nbsp;<math style="vertical-align: -5px">y=f(g(x))</math>&nbsp; is a differentiable function of &nbsp;<math style="vertical-align: 0px">x</math>&nbsp; and  
  
 
::<math>y'=f'(g(x))\cdot g'(x).</math>
 
::<math>y'=f'(g(x))\cdot g'(x).</math>
 
 
 
Taking the derivatives of <em>simple functions</em> (i.e. polynomials) is easy using the power rule.
 
 
For example, if &nbsp;<math style="vertical-align: -5px">f(x)=x^3+2x^2+5x+3,</math>&nbsp; then &nbsp;<math style="vertical-align: -5px">f'(x)=3x^2+4x+5.</math>
 
 
But, what about more <em>complicated functions</em>?
 
 
For example, what is &nbsp;<math style="vertical-align: -5px">f'(x)</math>&nbsp; when &nbsp;<math style="vertical-align: -5px">f(x)=\sin x \cos x?</math>
 
 
Or what about &nbsp;<math style="vertical-align: -5px">g'(x)</math>&nbsp; when &nbsp;<math style="vertical-align: -15px">g(x)=\frac{x}{x+1}?</math>
 
 
Notice &nbsp;<math style="vertical-align: -5px">f(x)</math>&nbsp; is a product, and &nbsp;<math style="vertical-align: -5px">g(x)</math>&nbsp; is a quotient. So, to answer the question of how to calculate these derivatives, we look to the Product Rule and the Quotient Rule. The Product Rule and the Quotient Rule give us formulas for calculating these derivatives.
 
 
'''Product Rule'''
 
 
Let &nbsp;<math style="vertical-align: -5px">h(x)=f(x)g(x).</math>&nbsp; Then,
 
 
::<math>h'(x)=f(x)g'(x)+f'(x)g(x).</math>
 
 
'''Quotient Rule'''
 
 
Let &nbsp;<math style="vertical-align: -19px">h(x)=\frac{f(x)}{g(x)}.</math>&nbsp; Then,
 
 
::<math>h'(x)=\frac{g(x)f'(x)-f(x)g'(x)}{(g(x))^2}.</math>
 
  
 
==Warm-Up==
 
==Warm-Up==

Revision as of 09:21, 9 October 2017

Introduction

It is relatively easy to calculate the derivatives of simple functions, like polynomials or trigonometric functions.

But, what about more complicated functions?

For example,    or  

Well, the key to calculating the derivatives of these functions is to recognize that these functions are compositions.

For    it is the composition of the function    with  

Similarly, for    it is the composition of    and  

So, how do we take the derivative of compositions?

The answer to this question is exactly the Chain Rule.

Chain Rule

Let    be a differentiable function of    and let    be a differentiable function of   

Then,    is a differentiable function of    and

Warm-Up

Calculate  

1)  

Solution:  
Using the Product Rule, we have
Then, using the Power Rule, we have
NOTE: It is not necessary to use the Product Rule to calculate the derivative of this function.
You can distribute the terms and then use the Power Rule.
In this case, we have
Now, using the Power Rule, we get
In general, calculating derivatives in this way is tedious. It would be better to use the Product Rule.
Final Answer:  
       
or equivalently
       

2)  

Solution:  

Using the Quotient Rule, we have

Then, using the Power Rule, we have
NOTE: It is not necessary to use the Quotient Rule to calculate the derivative of this function.
You can divide and then use the Power Rule.
In this case, we have
Now, using the Power Rule, we get
Final Answer:  
       
or equivalently
       

3)  

Solution:  
Using the Quotient Rule, we get
since    and  
Since    we have
Final Answer:  
       

Exercise 1

Calculate the derivative of  

First, we need to know the derivative of    Recall

Now, using the Quotient Rule, we have

Using the Product Rule and Power Rule, we have

So, we have

Exercise 2

Calculate the derivative of  

Notice that the function    is the product of three functions.

We start by grouping two of the functions together. So, we have  

Using the Product Rule, we get

Now, we need to use the Product Rule again. So,

So, we have

But, there is another way to do this problem. Notice

Now, you would only need to use the Product Rule once instead of twice.

Exercise 3

Calculate the derivative of  

Using the Quotient Rule, we have

Now, we need to use the Product Rule. So, we have

So, we get

Exercise 4

Calculate the derivative of  

First, using the Quotient Rule, we have

Now, we need to use the Product Rule. So, we have

So, we have